2021
DOI: 10.3389/fendo.2021.564781
|View full text |Cite
|
Sign up to set email alerts
|

Risks, Benefits, and Treatment Modalities of Menopausal Hormone Therapy: Current Concepts

Abstract: Menopausal hormone therapy (HT) prescribing practices have evolved over the last few decades guided by the changing understanding of the treatment’s risks and benefits. Since the Women’s Health Initiative (WHI) trial results in 2002, including post-intervention analysis and cumulative 18-year follow up, it has become clear that the risks of HT are low for healthy women less than age 60 or within ten years from menopause. For those who are experiencing bothersome vasomotor symptoms, the benefits are likely to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 107 publications
1
70
0
9
Order By: Relevance
“…Menopause is associated with the appearance of menopause symptoms, such as vasomotor symptoms (hot flushes and/or night sweats), genitourinary symptoms (vaginal dryness and atrophy, uterine bleeding and sexual dysfunction), urinary symptoms (incontinence and infections), mood change (irritability, anxiety, sadness, hyper-sensibility and depression), and cognitive disturbance [80,81]. In addition, menopause is also associated with an increased risk of cardiovascular diseases, bone fractures related to osteoporosis, and metabolic complications such as type-2 diabetes [82][83][84][85].…”
Section: Menopause Symptomsmentioning
confidence: 99%
“…Menopause is associated with the appearance of menopause symptoms, such as vasomotor symptoms (hot flushes and/or night sweats), genitourinary symptoms (vaginal dryness and atrophy, uterine bleeding and sexual dysfunction), urinary symptoms (incontinence and infections), mood change (irritability, anxiety, sadness, hyper-sensibility and depression), and cognitive disturbance [80,81]. In addition, menopause is also associated with an increased risk of cardiovascular diseases, bone fractures related to osteoporosis, and metabolic complications such as type-2 diabetes [82][83][84][85].…”
Section: Menopause Symptomsmentioning
confidence: 99%
“…Although it is known that estrogen treatment can be effective in stopping the loss of mineral content from bone in women after menopause, its administration as a treatment for osteoporosis is not currently recommended, due to the possibility of serious side effects and the existence of other safer alternatives. For this reason, estrogen therapy, as a hormonal treatment for menopause, is not recommended for the treatment of osteoporosis [18].…”
Section: Estrogensmentioning
confidence: 99%
“…Developing multi-targeted effective therapeutic measures for multifactorial T2D are on the hunt, estrogen therapy and NO therapy could be imaging as potential multi-targeted therapeutic strategy for T2D [52,54,55]. However, systemic delivery of estrogen /or NO agent potentially increase its serious adverse effects of estrogen/or NO agent toxicity [17,56]. Thus, it is potentially important in the clinical setting that Re produces multi-targeted potent antidiabetic effects via activation of ERα signaling pathway in the NO dependent manner described in the present study.…”
Section: Ginsenoside Re Is An Alternativementioning
confidence: 99%
“…Recently, numerous clinical and experimental studies have demonstrated that estrogen and 17β-estradiol (E2) characterize insulinotropic and multi-targeted antidiabetic effects that including anti-oxidative stress, anti-inflammation, antiapoptosis, enhances β-cell survival and generation , increases pancreatic insulin content, gene expression and insulin release ,reducing IR, glycemic and lipids control in various animal models and diabetes [11,12] by signaling through estrogen receptor (ER) alpha (ERα) /or ERβ [13,14]. It strongly suggests that estrogen and ER signaling pathway are potential multitargeting therapeutic candidate for diabetes therapy [15,16], but it has serious adverse events [17].…”
Section: Introductionmentioning
confidence: 99%